EMSIAN AND EIFELIAN REFERENCE SECTIONS OF MONGOLIA - Alekseeva R.E.; Goryunova R.V.; Ulitina L.M.; Erlanger O.A.; Aristov V.A. (My University, 1996)
Results of joint research on macrofauna and conodonts are presented in the paper. Based on new data, the relationship between conodont and regional zones was established for the first time, and boundaries between the stages under consideration were refined. The Mongolian sequences were correlated with reference sections of the Salair. The available data made possible wide interregional correlations of Mongolian sections characterized by endemic fauna.
Keywords: Emsian; Eifelian; Палеозой::Девонская::Нижний::Эмсский; Paleozoic::Devonian::Middle::Eifelian; Paleozoic::Devonian::Lower::Emsian; Палеозой::Девонская::Средний::Эйфельский